An Evaluation of the International Economic Order - الفيتوری , عطية (Dirasat in Economics and Business, 1981)
This paper discussed brienfly the present internatioinal economic order in light of its potentials and its problems. During the 70's many under-developed countries showed their dissatisfactions to continue and cooperate under the present international economic order, because the under-developed countries complained from the instability and the uncertainty created by the present economic order. This paper reviewed the reasons that made all the countries in this world to participate in the international trade, and it measured the importance of this relation' in terms of the increasing value of exports and imports, it gave another measure to this relation, which is the change in the international reserves (international liquidity). After this brief review, the paper discussed the problems which faced many countries and which are related to the international economic order. The countries which claimed to be hurt by the present economic order are the under-developed countries. Some of these problems are the mal-distribution of wealth among countries, the deteriorating terms of trade, problems related to the international monetary system, etc.